Banishment in the Late Medieval Eastern Netherlands Exile and Redemption in Kampen - Frankot, Edda (Springer Nature, 2022)
This open access book analyses the practice of banishment and what it can tell us about the values of late medieval society concerning morally acceptable behaviour. It focuses on the Dutch town of Kampen and considers the exclusion of offenders through banishment and the redemption of individuals after their exile. Banishment was a common punishment in late medieval Europe, especially for sexual offences. In Kampen it was also meted out as a consequence of the non-payment of fines, after which people could arrange repayment schemes which allowed them to return. The books firstly considers the legal context of the practice of banishment, before discussing punishment in Kampen more generally. In the third chapter the legal practice of banishment as a punitive and coercive measure is discussed. The final chapter focuses on the redemption of exiles, either because their punishment was completed, or because they arranged for the payment of outstanding fines.